2018
DOI: 10.7567/jjap.57.062401
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of radiophotoluminescence center formation mechanism in Ag-doped phosphate glasses

Abstract: Ag-doped phosphate glasses have widely been used as radiophotoluminescence (RPL) dosimeters. However, the RPL center formation process is not fully understood. In this study, we investigated the RPL center formation process in Ag-doped Na-Al phosphate glasses. We observed that two RPL centers (Ag 0 and Ag 2+ ) were formed at temperatures higher than 100 and 250 K, respectively. In addition, activation energies of their formation were estimated to be 20 and 267 meV, respectively. These results suggest that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…(14) Many researchers have reported the RPL behavior of FD-7 glass after radiation. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) In the RPL mechanism, the generated Ag species are the origin of the luminescence. Figure 2 shows PL spectra of the front (solid line) and back (dotted line) of FD-7 glass after positron irradiation for 5 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(14) Many researchers have reported the RPL behavior of FD-7 glass after radiation. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) In the RPL mechanism, the generated Ag species are the origin of the luminescence. Figure 2 shows PL spectra of the front (solid line) and back (dotted line) of FD-7 glass after positron irradiation for 5 days.…”
Section: Resultsmentioning
confidence: 99%
“…This glass has been used as glass badges for personal monitoring provided by Chiyoda Technol Corporation. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) It has been reported that the glass system exhibits radiophotoluminescence (RPL), (21)(22)(23)(24)(25)(26) a luminescence owing to electronic transitions within luminescent centers that are generated in phosphors by ionizing radiation. Radiation-induced effects in solid materials have been reported in a variety of fields.…”
Section: Introductionmentioning
confidence: 99%
“…This is a typical feature that the Ag-doped phosphate glass shows, a build-up of RPL signal, the origin of which is understood to be a thermally assisted formation of luminescent centers. 30,31) In fact, showing the build-up feature at room temperature makes a real-time dose measurement difficult; therefore, the RPL of Sm-doped CaSO 4 is very attractive for real-time dosimetry applications.…”
Section: Resultsmentioning
confidence: 99%
“…There are two types of dosimeters classified by different ways (energies) to stimulate carriers; thermally stimulated luminescence (TSL) dosimeter uses thermal stimulation, [12][13][14][15][16][17] and optically stimulated luminescence (OSL) dosimeter utilizes light stimulation. [18][19][20][21][22] In contrast, some dosimeters use a phenomenon called radio-PL, [23][24][25][26][27][28][29][30] in which luminescent centers corresponding to the irradiation doses are generated newly, and RPL can be easily measured by a PL technique. The most prominent RPL material is Ag-doped phosphate glass (RPL glass).…”
Section: Introductionmentioning
confidence: 99%